Melangkah Bersama: Menghidupkan Pancasila melalui Kurikulum Merdeka - Yoma Mochamad Mansur; Sukirman Sukirman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
The comprehensive consideration of curriculum in educational management is pivotal, particularly amidst the pursuit of higher quality learning through the phased implementation of an independent curriculum. Amidst prevalent challenges within the education sphere hindering the development of intelligent human resources with exemplary character, the adoption of an independent curriculum is seen as a strategic measure to address educational deficiencies by prioritizing student-centered learning processes. This research, utilizing a descriptive qualitative approach, focuses on analyzing the planning, organizing, actuating, and controlling aspects of implementing an independent curriculum. Conducted at Muhammadiyah 8 Middle School in Bandung City, data collection methods encompass interviews, documentation, and observations, further validated through data triangulation. The findings reveal the adoption of a potential and competency-based curriculum, with an emphasis on a learning model rooted in high order thinking skills (HOTS) and 21st-century competencies, including critical thinking, creativity, problem-solving, communication, and collaboration (4C). Additionally, the school integrates various character development programs, highlighting the impact of independent learning on realizing the six dimensions of the Pancasila Student Profile.